Strengthening Public Service Ethics in AI era: An Indonesian Perspective - Mastur, Anida Sri Rahayu; Ardi, Imma Yedida; Widayat, Wisnu; Setiawan, Agung (Dinasti International Journal of Economics, Finance & Accounting, 2026)
Digital transformation in public services, particularly through the use of artificial intelligence (AI), has the potential to significantly improve efficiency and the quality of services provided. While AI offers opportunities to accelerate processes, ethical concerns remain central, particularly with regard to fairness, privacy, supervision and accountability. This study uses the application of ethical principles in AI-based public service delivery at the Immigration Office of Kelas I Khusus TPI Semarang as a case study. Adopting a descriptive qualitative approach, the study explores how Indonesian public service officers embody principles such as honesty, trustworthiness, respect for individuals, protection of life, and justice within the framework of AI-assisted passport services. The findings reveal that, although AI has improved efficiency, challenges remain in ensuring equitable access to AI tools among employees, safeguarding personal data and maintaining transparent oversight. Stakeholder involvement and tiered supervision procedures are also crucial for sustaining accountability. Moreover, enhancing human resource preparedness and digital infrastructure is essential to ensure the equitable distribution of AI benefits across all levels of public service. This research provides valuable insights into strengthening the ethical foundations of AI implementation within the public sector, proposing strategic measures to enhance fairness and transparency in Indonesian public service delivery.